Turkish translation in the steam translation server :|two case studies on video game localisation - Sarıgül, Semih. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
As a sub-discipline of AVT, VGL has become a popular research topic around the world in the last decade. In addition to professional localisation service companies, volunteer and non-professional communities also play an important role in VGL processes in the world. However, in Turkey, despite the existence of both volunteer communities and professional localisation companies, academic studies on VGL are scarce. To fill this gap in the existing literature, the present study focuses on the STS as a volunteer VGL platform and a volunteer VGL community, i.e. TTC, and a professional VGL company, i.e. 23Studios, within it. To this aim, two different VGL projects by these groups, i.e. Dota 2 and W3WH, were analysed as case studies to explore similarities and differences between professional and non-professional VGL practices in the STS in Turkey. First, a participant observation was conducted to understand how translation crowdsourcing was used in the STS. Later, an online survey was carried out to investigate volunteer STS translators’ demographic profiles, understanding of translation and localisation and individual VGL experiences. Later, two different group interviews were held with TTC and 23Studios to explore non-professional and professional VGL processes in detail. The survey and interview findings demonstrated that volunteer translators in the STS displayed a homogenous profile to a certain extent and that VGL practices in both interviewed groups displayed significant differences in terms of process management and the use of technical facilities in the STS.
Keywords: Translators (Computer programs); Steam.